Small Molecules as Anti-TNF Drugs - Richmond, Victoria; M. Michelini, Flavia; A. Bueno, Carlos; E. Alche, Laura; A. Ramirez, Javier (Current Medicinal Chemistry, 2015)
Tumor necrosis factor (TNF, TNF-α, cachectin) is a pleiotropic, proinflammatory cytokine with multiple biological effects, many of which are not yet fully understood. Although TNF was initially described as an anti-tumor agent more than three decades ago, current knowledge places it central to immune system homeostasis. TNF plays a critical role in host defense against infection, as well as an inhibitory role in autoimmune disease. However, TNF overproduction generates deleterious effects by inducing the transcription of genes involved in acute and chronic inflammatory responses including asthma, rheumatoid arthritis, Crohn´s disease, and psoriasis. Direct inhibition of TNF by biologics, such as monoclonal antibodies and circulating TNF receptor constructs, has produced effective treatments for these disorders and validated the inhibition of this proinflammatory cytokine as an effective therapy. Unfortunately, these biological therapies suffer from several drawbacks, including high cost and the induction of autoantibody production. Thus, the development of small molecules able to modulate TNF production or signaling pathways remains a central challenge in Medicinal Chemistry. Considerable efforts have been made over the past two decades to develop such inhibitors, which could potentially be administered orally and would presumably be cheaper. This review is focused on the recent development of compounds that modulate the activity of this cytokine by acting at different levels, such as TNF expression, processing, binding to its receptors and direct inhibition. These approaches will be compared and discussed.
Keywords: Cytokines